2011
DOI: 10.1016/j.snb.2011.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Glassy carbon electrode modified with hybrid films containing inorganic molybdate anions trapped in organic matrices of chitosan and ionic liquid for the amperometric sensing of phosphate at neutral pH

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. at neutral pH , hence would be applicable for pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…It was reported that the peak around +400 mV involves exchange of two electrons and was attributed to MoMo(VI)/Mo(IV) and the peak around 100 mV involves three electrons and was attributed to Mo (IV)/Mo (I) 28,29. Each electron transfer is associated to the addition of a proton 30. The magnitude of signal of these redox peaks increase drastically when molybdate is mixed with phosphate or silicate at pH≤2 allowing formation of molybdophosphate and molybdosilicate complexes 26,28,29,31.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the peak around +400 mV involves exchange of two electrons and was attributed to MoMo(VI)/Mo(IV) and the peak around 100 mV involves three electrons and was attributed to Mo (IV)/Mo (I) 28,29. Each electron transfer is associated to the addition of a proton 30. The magnitude of signal of these redox peaks increase drastically when molybdate is mixed with phosphate or silicate at pH≤2 allowing formation of molybdophosphate and molybdosilicate complexes 26,28,29,31.…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of signal of these redox peaks increase drastically when molybdate is mixed with phosphate or silicate at pH≤2 allowing formation of molybdophosphate and molybdosilicate complexes 26,28,29,31. The measurement of signal of these peaks was the basis of electrochemical determination of phosphate 26,28,30,31 and silicates 19,26.…”
Section: Resultsmentioning
confidence: 99%
“…The use of Amperometric sensors, that measure the current produced by the target analyte at an electrode with a constant voltage, has also been investigated widely (Beer et al, 1996(Beer et al, , 1997 showing some selectivity for dihydrogen phosphate and orthophosphate. Some involved measuring the reduction of the ammonium phosphomolybdate complex formed in the standard phosphomolybdate reaction (Quintana et al, 2004;Udnan et al, 2005) or anodic oxidation of molybdenum (Jonca et al, 2011), while others involved the use of electrodes embedded with ammonium molybdate (Berchmans et al, 2011). Others involved the use of phosphate sensitive enzyme electrodes, designed for potential environmental applications, and are able to detect orthophosphates down to 3 µg/L (Midgley, 1986;Engblom, 1998;Villalba et al, 2009;Rahman et al, 2006).…”
Section: Electrochemical Sensor Methodologies For Phosphate Detectionmentioning
confidence: 99%
“…Various electroanalytical methods available in literature were assessed for their advantages in terms of selectivity, simplicity, miniaturization, adaptability, and suitability for field measurements. Berchmans et al (2011) reported an amperometric method for phosphate analysis based on the use of a surface modified glassy carbon electrode. The linear range of detection for phosphate is between 19 and 100 pM with the first electrode configuration.…”
Section: Introductionmentioning
confidence: 99%